Modeling and Simulation of Methylene Blue Batch Adsorption Using Jatropha Curcas L. Residue-Based Activated Carbon by Shrinking Core Model - Yansen Hartanto (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Physic nut residue is one of bio-wastes which contains enough carbon can be processed further into other products with higher usage and economical value. One of the products is activated carbon which used commonly in chemical industry. Information regarding the kinetics describing mechanism and characteristic of adsorption using physic nut residue-based activated carbon can be obtained through modeling. Model used in this research are Pore-Surface Diffusion Model (PSDM) and Film-Pore Diffusion Model (FPDM) derived based on shrinking core model. This research begins with estimating the value of kf, Ds, and Dp parameters which later will be validated and simulated using various correlations and the model. Variations are done towards three variables: initial aqueous phase concentration (C0), pH value, and adsorbent types. The result shows PSDM is more accurate in representing the mass transfer characteristics of methylene blue adsorption using activated carbon synthesized from physic nut residue because the model prediction fit the experimental data better than the FPDM. The value of Ds ranged from 3, 99E-14 to 7, 66 E-14 while the value of Dp ranged from 9, 98E-13 to 2, 82E-12 . It is also found that value of Ds and Dp are affected by variables mentioned before.